Factors associated with villus atrophy in symptomatic coeliac disease patients on a gluten‐free diet. Issue 8 (20th February 2017) - Mahadev, S.; Murray, J. A.; Wu, T.‐T.; Chandan, V. S.; Torbenson, M. S.; Kelly, C. P.; Maki, M.; Green, P. H. R.; Adelman, D.; Lebwohl, B.
Summary: Background: Duodenal injury persists in some coeliac disease patients despite gluten‐free diet, and is associated with adverse outcomes. Aim: To determine the prevalence and clinical risk factors for persistent villus atrophy among symptomatic coeliac disease patients. Methods: A nested cross‐sectional analysis was performed on coeliac disease patients with self‐reported moderate or severe symptoms while following a gluten‐free diet, who underwent protocol‐mandated duodenal biopsy upon enrolment in the CeliAction clinical trial. Demographic factors, symptom type, medication use, and serology were examined to determine predictors of persistent villus atrophy. Results: Of 1345 symptomatic patients, 511 (38%, 95% CI, 35–41%) were found to have active coeliac disease with persistent villus atrophy, defined as average villus height to crypt depth ratio ≤2.0. On multivariable analysis, older age (OR, 5.1 for ≥70 vs. 18–29 years, 95% CI, 2.5–10.4) was a risk factor while longer duration on gluten‐free diet was protective (OR, 0.37, 95% CI, 0.24–0.55 for 4–5.9 vs. 1–1.9 years). Villus atrophy was associated with use of proton‐pump inhibitors (PPIs; OR, 1.6, 95% CI, 1.1–2.3), non‐steroidal anti‐inflammatory drugs (NSAIDs; OR, 1.64, 95% CI, 1.2–2.2), and selective serotonin reuptake inhibitors (SSRIs; OR, 1.74, 95% CI, 1.2–2.5). Symptoms were not associated with villus atrophy after adjusting for covariates. Conclusions: A majority of symptomatic coeliac disease patients did not have active disease on follow‐up histology. Symptoms were poorly predictive of persistent mucosal injury. The impact of NSAIDs, PPIs, and SSRIs on mucosal healing in coeliac disease warrants further study. Abstract : Linked Content This article is linked to Braude, Newnham and Mahadev et al papers. To view these articles visit https://doi.org/10.1111/apt.14055 and https://doi.org/10.1111/apt.14086 .